2006
DOI: 10.1017/s1049023x00003630
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Post-Traumatic Stress Disorder among Relief Force Workers after the Tsunami in Asia: Do Rescuers Become Victims?

Abstract: Objective:The objective of this study was to evaluate the frequency of posttraumatic stress disorder (PTSD) among the participants of the Turkish Red Crescent Disaster Relief Team after the Tsunami in Asia.Methods:The Clinician Administered PTSD Scale-1 (CAPS-1) was administered to 33 of 36 team members one month after their Disaster Relief Team duty. Along with the CAPS-1 interview, demographic features, profession, previous professional experience, previous experience with traumatic events and disasters also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 13 publications
4
64
0
Order By: Relevance
“…This estimated prevalence of those meeting criteria for PTSD in our sample is consistent with the range of 4% [15] to 24% [7] found in similar samples of civilians caregivers and medical personnel. Likewise, it is consistent with recent reports on rates of PTSD among military medical personnel serving in the IDF during the second Intifida (8.1%) [16] and in the U.S. forces in Iraq (6%) (Operation Iraqi Freedom Mental Health Advisory Team (MHAT).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This estimated prevalence of those meeting criteria for PTSD in our sample is consistent with the range of 4% [15] to 24% [7] found in similar samples of civilians caregivers and medical personnel. Likewise, it is consistent with recent reports on rates of PTSD among military medical personnel serving in the IDF during the second Intifida (8.1%) [16] and in the U.S. forces in Iraq (6%) (Operation Iraqi Freedom Mental Health Advisory Team (MHAT).…”
Section: Discussionsupporting
confidence: 90%
“…[3] Similar low rates of PTSD (0%-4%) were found in other studies that examined the relationship between secondary traumatization and occupational role among trauma counselors. [4][5][6] On the other hand, rates of PTSD among relief workers exposed to the Tsunami [7] and the earthquake in Taiwan [8,9] were once again in the 20% to 24% range. Interpretation of these contradictory results is difficult due to the great variability in the nature and severity of the actual trauma (there is a big difference between tending to injured and dead victims and watching similar sights on TV), assessment tools, and time intervals that elapsed from the disaster.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of PTSD among military and police personnel have found prevalence estimates of 8.3% (Defence Health 2016) and 10-12% (Rose et al 2002) for these populations respectively, compared with 4-6% of the general population (Cooper et al 2014). Whilst studies of HA workers have generally relied on questionnaire measures rather than structured clinical interviews (producing estimates of "probable PTSD" rather than formal diagnoses), indicative rate estimates for PTSD among national and international expatriate HA workers range between 17 and 30% in the available literature (Eriksson et al 2001;Armagan et al 2006;Putman et al 2009;Zhen et al 2012). …”
Section: Mental Health Comparisons Between Humanitarian Aid and Emergmentioning
confidence: 99%
“…The long period of rehabilitation will make the patients to fall into the post traumatic stress disorder (PTSD) as well as into infectious diseases, and it may occur not only to the victims but also to the relief forces and medical workers. By this reasons, limiting the work of the medical team involved in humanitarian assistance operations in the tsunami affected area is very important [11]. Helping children after tsunami is also another challenge for the medical team.…”
Section: Discussionmentioning
confidence: 99%